Phō̜rō̜bō̜. Pā Chumchon kap thāngʻō̜k khō̜ng sangkhom Thai : sitthi chumchon khon yū kap pā - Kitichai Rattana (Sathāban Chumchon Thō̜ngthin Phatthanā, 2004)
Laws concerning the community and the forest and the rights of the people living in the protected areas in Thailand.